Implicitly measured aggressiveness self-concepts in women with borderline personality disorder as assessed by an Implicit Association Test. (March 2020) - Baumann, Erik; Schmidt, Alexander F.; Jelinek, Lena; Benecke, Cord; Spitzer, Carsten
Abstract: Background: Aggressiveness resulting from inappropriately intense anger plays a major role in borderline personality disorder (BPD) and research using self-report measures has consistently found elevated levels of aggression in this condition. However, while self-report assesses explicit dimensions of the self-concept, it cannot elucidate implicit processes that are at least equally important as they guide the perceptions of the self and influence behavioral responses. The present study aimed to extend the research on aggressiveness self-concepts in BPD utilizing an indirect latency-based measure. Methods: Twenty-nine female inpatients with BPD and 21 healthy women were assessed with an aggressiveness self-concept Implicit Association Test (Agg-IAT) using reaction time measurements to determine the relative strengths of associations between the self vs. others and aggression vs. peacefulness. Additionally, participants completed self-report questionnaires capturing aggressiveness and BPD symptoms. Results: Women with BPD had a significantly more aggressive self-concept as indicated by the Agg-IAT than the control group. Moreover, they rated themselves significantly more aggressive on all dimensions than the controls. As expected, correlations between the Agg-IAT and the self-reported aggressiveness dimensions were low (mean r  = -.31). Limitations: The modest sample size and the disregard of a clinical control group limit the generalizability and specificity of our findings. Conclusions: This study extends prior findings on aggression in BPD in that women with BPD do not only explicitly conceive themselves as more aggressive, but also exhibit implicitly more aggressive self-concepts than healthy controls. Because implicit and explicit self-related operations are related, but distinct processes, our results may hold clinical and therapeutic implications. Highlights: Aggressiveness is a key feature in borderline personality disorder. Implicit processes contribute to an aggressiveness self-concept in this disorder. Explicit and implicit operations of the self are related, but distinct processes. Strategies targeting the implicit self-concept of these patients may be beneficial.